Copper-based catalyst for hydrogen production by methanol steam reforming and preparation method and application thereof

By loading copper complexes and transition metal oxides on porous carriers, the problems of poor stability and high carbon monoxide selectivity of copper-based catalysts in the process of hydrogen production by methanol steam reforming are solved, achieving high efficiency and stability of the catalyst, and Meets hydrogen quality requirements.

CN119346125APending Publication Date: 2025-01-24NANCHANG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411421949.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing copper-based catalysts have poor stability during the reforming of methanol water vapor in hydrogen production, and the selectivity of carbon monoxide in the product gas is relatively high, making it difficult to meet the requirements of proton exchange membrane fuel cells for hydrogen quality.

Method used

The porous carrier loading copper complexes and transition metal oxides are used to adjust the load capacity of copper elements and the Moorbi of the transition metal element to improve the catalytic activity and stability of the catalyst, while reducing the selectivity of carbon monoxide.

Benefits of technology

The catalytic activity and stability of the copper-based catalyst are significantly improved, the volume fraction of carbon monoxide in the product gas is reduced, and the hydrogen quality requirements of the proton exchange membrane fuel cell are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346125A_ABST
    Figure CN119346125A_ABST
Patent Text Reader

Abstract

The invention provides a methanol steam reforming hydrogen production copper-based catalyst and a preparation method and application thereof, and relates to the technical field of energy catalysis. The copper-based catalyst provided by the invention comprises a porous carrier as well as a copper compound and a transition metal oxide which are loaded on the surface of the porous carrier, the loading amount of the copper element in the copper compound on the copper-based catalyst is 5-30%; the molar ratio of the copper element in the copper compound to the transition metal element in the transition metal oxide is (0.1-1.8): 1. The methanol conversion rate of the catalyst at 260 DEG C reaches up to 94.3%, the CO2 selectivity is higher than 99.7%, and the catalyst is simple in synthesis process, free of synthesis wastewater, low in cost, capable of continuously and stably producing hydrogen and capable of meeting the hydrogen purity requirement of a fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy catalysis technology, and in particular to a copper-based catalyst for hydrogen production by methanol steam reforming, and a preparation method and application thereof. Background Art

[0002] As the global energy crisis and environmental pollution become increasingly severe, it is imperative to find clean and efficient energy carriers. Hydrogen energy, as a clean energy, has the advantages of high energy density and pollution-free combustion products, which is of great significance for reducing greenhouse gas emissions and improving energy efficiency. However, in the commercialization process of hydrogen energy, hydrogen storage and transportation are inconvenient, and the hydrogen energy infrastructure is not perfect. Using methanol water vapor for on-site reforming hydrogen production is a feasible hydrogen production solution. The generated hydrogen is supplied to proton exchange membrane fuel cells to output electricity. This method can greatly improve the application scenarios and portability of hydrogen energy.

[0003] However, one of the key elements of methanol steam reforming to produce hydrogen is the catalyst. Since the reforming hydrogen production reaction is an endothermic reaction, it needs to be carried out at a certain temperature and pressure. The use of catalysts can greatly reduce the restrictions on the reaction environment. At the same time, in order to meet the requirements of proton exchange membrane fuel cells for the quality of the produced hydrogen, the catalyst needs to be able to produce hydrogen stably for a long time and reduce the volume fraction of carbon monoxide in the product gas to avoid proton exchange membrane fuel cell poisoning.

[0004] At present, the catalysts commonly used in methanol steam reforming hydrogen production reactions mainly include copper-based catalysts and precious metal catalysts. Compared with precious metal catalysts, copper-based catalysts have mild reaction conditions, good reforming activity and low cost, and are easy to be applied on a large scale in industry. However, the copper-based catalysts commonly used in the prior art have poor stability during long-term use, and the selectivity of carbon monoxide in the product gas is high, so it is urgent to provide a solution to improve the above problems. Summary of the invention

[0005] The purpose of the present invention is to provide a copper-based catalyst for producing hydrogen through steam reforming of methanol, and a preparation method and application thereof.

[0006] In the first aspect, the present invention provides a copper-based catalyst for hydrogen production by methanol steam reforming, comprising a porous carrier and a copper complex and a transition metal oxide loaded on the surface of the porous carrier; the loading amount of the copper element in the copper complex on the copper-based catalyst is 5-30%; the molar ratio of the copper element in the copper complex to the transition metal element in the transition metal oxide is (0.1-1.8):1.

[0007] The copper-based catalyst provided by the present invention adopts a copper complex as an active ingredient, and the transition metal oxide can improve the dispersion of the copper complex on the porous carrier and improve the redox property of the copper complex, thereby improving the overall catalytic activity and catalytic performance stability of the copper-based catalyst. At the same time, the use of the copper complex and the transition metal oxide can reduce the selectivity for carbon monoxide.

[0008] Optionally, the copper composite comprises elemental copper nanoparticles.

[0009] Optionally, the copper composite is generated by reducing copper oxide in a reducing atmosphere.

[0010] Optionally, the transition metal element in the transition metal oxide is at least one of chromium, niobium, tantalum and vanadium.

[0011] Optionally, the transition metal oxide includes transition metal ions in at least two valence states.

[0012] Optionally, the porous carrier includes at least one of an alumina carrier, a cerium oxide carrier, a zirconium oxide carrier, a molybdenum carbide carrier, a silica carrier, and a molecular sieve.

[0013] Optionally, the specific surface area of ​​the porous carrier is 180-200m 2 / g.

[0014] Optionally, the source of the copper complex includes at least one of copper nitrate, copper sulfate, and copper chloride.

[0015] Optionally, the source of the transition metal oxide includes at least one of a transition metal nitrate and a transition metal organic salt.

[0016] In a second aspect, the present invention also provides a method for preparing any of the above-mentioned optional copper-based catalysts, comprising: mixing a porous carrier in a mixed solution of copper ions and transition metal ions and then evaporating the solvent to obtain a catalyst precursor, and high-temperature oxidizing the catalyst precursor and then reducing it to obtain a copper-based catalyst.

[0017] Optionally, the molar ratio of copper ions to transition metal ions in the mixed solution is (0.1-1.8):1.

[0018] Alternatively, the porous support is mixed in a mixed solution at 20-30°C.

[0019] Optionally, the porous carrier is mechanically mixed in the mixed solution for 2-3 hours and then the solvent is evaporated. The mechanical mixing includes one of ultrasonic mixing, stirring mixing and oscillating mixing.

[0020] Optionally, after the porous carrier is mixed in the mixed solution, the solvent is evaporated at 75-90°C.

[0021] Optionally, the catalyst precursor is obtained by evaporating the solvent and then drying.

[0022] Optionally, the catalyst precursor is prepared by evaporating the solvent and grinding the mixture through a 40-60 mesh screen.

[0023] Optionally, the average particle size of the catalyst precursor is 250-380 μm.

[0024] Optionally, the catalyst precursor is oxidized in an oxygen-containing atmosphere at 350-450°C.

[0025] Optionally, the catalyst precursor is oxidized at high temperature for 3-5 h.

[0026] Optionally, the catalyst precursor is subjected to high temperature oxidation and then reduced in a reducing atmosphere with a hydrogen content of 5-15 vol. %.

[0027] Optionally, the catalyst precursor is subjected to high temperature oxidation and then reduced in a reducing atmosphere for 30-50 minutes.

[0028] Optionally, the catalyst precursor is subjected to high-temperature oxidation and then reduced in a reducing atmosphere at 250-350°C.

[0029] In a third aspect, the present invention further provides the use of any of the above optional copper-based catalysts or the copper-based catalysts prepared by any of the above optional preparation methods in hydrogen production by steam reforming of methanol.

[0030] Optionally, when producing hydrogen by methanol steam reforming, a methanol steam mixture is introduced at 200-260° C. and catalyzed by a copper-based catalyst to react and generate hydrogen.

[0031] Optionally, the methanol-water vapor mixture includes an inert carrier gas.

[0032] Optionally, the molar ratio of methanol to water in the methanol-water vapor mixture is 1:(1-2).

[0033] Optionally, hydrogen, carbon dioxide and carbon monoxide are generated by reaction under the catalysis of a copper-based catalyst, and the volume fraction of the carbon monoxide is less than or equal to 3 ppm.

[0034] Optionally, the methanol-water vapor mixture is heated for 20-30 hours. -1 The weight airspeed is entered. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 XRD characterization diagrams of the catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 4 of the present invention;

[0036] Figure 2The Raman spectra of the catalytic intermediates obtained in Examples 1 to 4 and Comparative Examples 1 to 4 of the present invention are as follows;

[0037] Figure 3 It is the H2-TPR characterization diagram of the catalytic intermediates prepared in Examples 1 to 4 and Comparative Examples 1 to 4 of the present invention;

[0038] Figure 4 The methanol conversion curves at different temperatures of the catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 2 of the present invention when performing methanol steam reforming hydrogen production reaction;

[0039] Figure 5 The methanol conversion curves at different temperatures of the catalysts prepared in Examples 2 and 5 to 8 of the present invention when performing methanol steam reforming hydrogen production reaction;

[0040] Figure 6 The methanol conversion curves at different temperatures of the catalysts prepared in Examples 6, 9 and 11 of the present invention when performing methanol steam reforming hydrogen production reaction;

[0041] Figure 7 The methanol conversion curves at different temperatures of the catalysts prepared in Examples 12 to 17 of the present invention when performing methanol steam reforming hydrogen production reaction;

[0042] Figure 8 This is a graph showing changes in methanol conversion and hydrogen production rate when the catalyst prepared in Example 2 of the present invention is subjected to a methanol steam reforming hydrogen production reaction for 90 hours. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.

[0044] The present invention provides a copper-based catalyst for hydrogen production by methanol steam reforming, comprising a porous carrier and a copper compound and a transition metal oxide loaded on the surface of the porous carrier. In fact, since the porous carrier has a porous structure, the loading capacity of the copper compound and the transition metal oxide can be greatly improved, and the copper compound and the transition metal oxide can be dispersed in the pores of the porous carrier.

[0045] Specifically, when the methanol steam reforming reaction is carried out to produce hydrogen, the copper complex, as the main active ingredient, catalyzes the reforming reaction, and the transition metal oxide promotes the dispersion of the copper complex on the surface of the porous carrier, thereby enhancing the redox properties of the copper-based catalyst, thereby improving the overall catalytic activity and stability of the catalyst.

[0046] Specifically, the loading amount of copper element in the copper complex on the copper-based catalyst is 5-30%. In fact, by adjusting the loading amount of the copper complex on the porous carrier, the dispersion degree of the copper complex on the porous carrier can be adjusted, and the catalytic activity of the copper-based catalyst in the reforming reaction can be effectively controlled.

[0047] Specifically, the molar ratio of the copper element in the copper complex on the porous carrier to the transition metal element in the transition metal oxide is (0.1-1.8): 1. By adjusting the amount of transition metal elements and copper elements, the dispersion-promoting performance of transition metal elements on the copper complex can be effectively utilized to enhance the dispersion of the copper complex on the surface of the porous carrier, and at the same time, the anchoring effect of the copper complex and the porous carrier can be enhanced. In addition, the amount of different transition metal elements and copper elements will affect the conversion rate of methanol in the methanol steam reforming reaction of the copper-based catalyst.

[0048] In fact, the copper complex includes elemental copper nanoparticles. During the methanol steam reforming reaction, elemental copper nanoparticles can provide suitable active sites and electronic environment, activate methanol molecules, promote the conversion of intermediate products, participate in the water-gas shift reaction, and promote the desorption of hydrogen on the surface of the copper-based catalyst, thereby efficiently generating product gas.

[0049] In some embodiments, the copper composite is generated by reducing copper oxide under a reducing atmosphere. In fact, by reducing in a reducing atmosphere, copper nanoparticles can be generated in situ on the surface of the porous support. At the same time, due to the difference in the degree of reduction, some copper oxide that has not been reduced still exists in the copper composite. Specifically, before reducing the copper oxide, the copper oxide is uniformly attached to the surface of the porous support by an impregnation method or other common methods.

[0050] In some embodiments, the transition metal element in the transition metal oxide is at least one of chromium, niobium, tantalum, and vanadium. In fact, the selection of different transition metal oxides will have different effects on the catalytic performance of the copper-based catalyst. This may be because different transition metal oxides have different electronic configurations and valence states, which will affect the electronic structure of copper through electronic interactions, thereby affecting the overall catalytic performance of the copper-based catalyst.

[0051] In some embodiments, the transition metal oxide includes at least two transition metal ions of valence state. In fact, when the copper oxide is reduced in a reducing atmosphere, the copper oxide supported on the transition metal oxide will also be reduced to form an intermediate valence oxide with a complex valence state.

[0052] In some embodiments, the porous carrier includes at least one of an alumina carrier, a cerium oxide carrier, a zirconium oxide carrier, a molybdenum carbide carrier, a silicon dioxide carrier, and a molecular sieve. In fact, the porous carrier can be selected from inorganic porous materials commonly used in the art for catalytically active loading, as long as the copper complex and the transition metal oxide can be loaded. Specifically, the specific surface area of ​​the porous carrier is 180-200 m 2 / g.

[0053] In some embodiments, the source of the copper complex includes at least one of copper nitrate, copper sulfate, and copper chloride. In fact, when forming the copper complex on a porous support, the copper element can be loaded on the surface of the porous support by various means, such as impregnating the copper salt on the surface of the porous support by an impregnation method. Similarly, the source of the transition metal oxide includes at least one of a transition metal nitrate and a transition metal organic salt.

[0054] The present invention also provides a method for preparing the copper-based catalyst in any of the above embodiments, comprising: mixing a porous carrier in a mixed solution of copper ions and transition metal ions, evaporating the solvent to obtain a catalyst precursor, and then high-temperature oxidizing the catalyst precursor and then reducing it to obtain a copper-based catalyst.

[0055] In fact, when the porous carrier is mixed in the mixed solution, the copper ions and transition metal ions are evenly diffused into the pore structure of the porous carrier, and interact with the surface of the porous carrier through physical adsorption and chemical adsorption. At the same time, the co-impregnation method can promote the uniform interweaving and distribution of copper ions and transition metal ions on the surface of the porous carrier.

[0056] In some embodiments, the molar ratio of copper ions to transition metal ions in the mixed solution is (0.1-1.8): 1. This facilitates the copper salt and transition metal salt dissolved in the mixed solution to be uniformly impregnated on the surface of the porous support at a preset molar ratio after the solvent is evaporated. Specifically, the solvent in the mixed solution must be able to completely dissolve the copper salt and the transition metal salt and not react with them.

[0057] In some embodiments, the porous carrier is mixed in a mixed solution at 20-30° C. In fact, when the porous carrier is mixed with the mixed solution, the higher the temperature of the mixed solution within a certain range, the more conducive it is to improving the surface activity of the porous carrier, thereby facilitating the impregnation of copper ions and transition metal ions on the surface. However, from the perspective of economy and convenience, mixing the porous carrier with the mixed solution at room temperature can also achieve good results.

[0058] Specifically, the porous carrier is mechanically mixed in the mixed solution for 2-3 hours and then the solvent is evaporated. More specifically, the mechanical mixing method used includes ultrasonic mixing, stirring mixing, and oscillating mixing. In fact, when ultrasonic mixing is used, the ultrasonic cavitation effect can be used to avoid the agglomeration of the porous carrier in the mixed solution. In addition, it is beneficial to remove the gas in the pores of the porous carrier, which is beneficial to the impregnation of the mixed solution.

[0059] In some embodiments, after the porous carrier is mixed in the mixed solution, the solvent is evaporated at 75-90°C. This is beneficial to the loading of the copper salt and transition metal salt in the mixed solution on the surface of the porous carrier. At the same time, adjusting the evaporation temperature of the mixed solution can speed up the efficiency while avoiding the destruction of the porous carrier and the morphology of the copper salt and transition metal salt on the surface due to the boiling of the solution.

[0060] In some embodiments, after the porous carrier is mixed in the mixed solution and the solvent is evaporated, the obtained solid is dried, which is conducive to reducing the water content of the solid and facilitating reduction. In fact, the solid is ground and sieved after drying, which is conducive to improving the uniformity of the particle size of the catalyst precursor. Specifically, after grinding, the solid is sieved through a 40-60 mesh screen, so that the average particle size of the catalyst precursor is 250-380 μm.

[0061] In fact, the porous carrier is mixed in the mixed solution and the solvent is evaporated and then dried. If the particle size of the solid is too small after grinding, it can be pressed into tablets to avoid the solid powder from sintering into blocks during the subsequent sintering process.

[0062] In some embodiments, the catalyst precursor is oxidized in an oxygen-containing atmosphere at 350-450° C., so that the copper salt and transition metal salt attached to the surface of the porous support can be oxidized into copper oxide and transition metal oxide, and the stability of the copper oxide and transition metal oxide on the surface of the porous support can be improved by high-temperature oxidation roasting. Specifically, the oxygen content in the oxygen-containing atmosphere is 20-100%. More specifically, the oxygen-containing atmosphere can be an air atmosphere.

[0063] In some embodiments, the catalyst precursor is oxidized at high temperature for 3-5 hours, which is beneficial to completely convert the copper salt and transition metal salt on the surface of the catalyst precursor into copper oxide and transition metal oxide. At the same time, long-term high-temperature heat treatment can calcine the copper oxide, transition metal oxide and porous carrier together, which is beneficial to improve the long-term catalytic stability of the copper-based catalyst in the catalytic environment.

[0064] Specifically, the catalyst precursor is subjected to oxidation treatment at high temperature and then subjected to reduction treatment in a reducing atmosphere with a hydrogen content of 5-15 vol.%. In fact, the copper oxide on the surface of the porous support obtains electrons in the hydrogen, thereby generating copper nanoparticles in situ. In addition, the valence state of the transition metal element in the transition metal oxide can be reduced in the hydrogen.

[0065] In some embodiments, the catalyst precursor is reduced in a reducing atmosphere for 30-50 minutes, specifically, the catalyst precursor is reduced in a reducing atmosphere at 250-350° C. In fact, the reducing atmosphere also includes a residual amount of inert gas, such as argon, helium, and neon.

[0066] The present invention also provides an application of a copper-based catalyst in hydrogen production by methanol steam reforming, comprising introducing a methanol steam mixed gas to react and generate hydrogen under the catalysis of a copper-based catalyst at 200-260°C. In fact, during the reforming hydrogen production reaction, the product gas produced also includes carbon dioxide and a trace amount of carbon monoxide.

[0067] Specifically, in the reforming hydrogen production reaction using the copper-based catalyst provided by the present invention, the carbon oxide gas in the product gas is less than or equal to 3 ppm, has extremely low carbon monoxide selectivity, and can well meet the requirements of the proton exchange membrane fuel cell for the product gas.

[0068] In some embodiments, when the methanol-water vapor mixture is introduced, the methanol and water vapor are transported to the position of the copper-based catalyst by an inert carrier, and specifically, the inert carrier gas can be argon. In fact, the molar ratio of methanol to water in the methanol-water vapor mixture is 1:(1-2). By setting an excess of relatively cheap water, the reforming reaction is facilitated to proceed in the forward direction and the conversion rate of methanol is improved.

[0069] In some embodiments, when the methanol-water vapor mixed gas is reformed to produce hydrogen, the methanol-water vapor mixed gas is heated for 20-30 hours. -1 The weight space velocity is passed into the copper-based catalyst and reacts with the copper-based catalyst. In fact, the weight space velocity indicates the gas mass of the methanol-water vapor mixture treated by the copper-based catalyst per unit mass per unit time, reflecting the residence time of the methanol-water vapor mixture at the copper-based catalyst.

[0070] Specifically, when reforming a methanol-water vapor mixture to produce hydrogen, a copper-based catalyst is loaded in the middle of a fixed-bed quartz tube reactor, and after preheating and activating the copper-based catalyst at 200-260°C, a high-pressure constant-flow pump is used to introduce a methanol-water mixed solution into a vaporization chamber, and an inert gas is used as a carrier gas to transport the methanol-water vapor mixture into the quartz tube reactor for catalytic reforming.

[0071] Example 1

[0072] This embodiment 1 provides a method for preparing a copper-based catalyst for hydrogen production by methanol steam reforming, comprising the following steps:

[0073] S1. Weigh 0.543 g (2.25 mmol) of copper nitrate trihydrate and 0.053 g (0.132 mmol) of chromium nitrate nonahydrate, stir and dissolve them in 10 mL of deionized water to prepare a mixed solution, then add 1.850 g of alumina powder (needle-shaped γ-alumina purchased from Sinopharm Chemical Reagent Co., Ltd.) and mix them under magnetic stirring at room temperature of 25° C. for 3 h to prepare a mixed suspension;

[0074] S2, after the mixed suspension is stirred and evaporated to dryness in a water bath at 80°C, the obtained solid is dried in a hot air drying oven at 80°C for 12 hours and after constant weight is reached, the dried solid is ground and passed through a 50-mesh sieve to obtain a catalyst precursor;

[0075] S3, transferring the catalyst precursor into a muffle furnace, heating it from room temperature to 400°C at a rate of 2°C / min in an air atmosphere, calcining it at 400°C for 4 hours, and then cooling it to room temperature with the furnace to obtain a catalytic intermediate;

[0076] S4. The catalytic intermediate is transferred to an atmosphere furnace, and the temperature is raised to 300°C at a rate of 2°C / min under an argon atmosphere and preheated for 1 hour. A 10 vol.% mixture of hydrogen and argon is introduced into the atmosphere furnace and the furnace is kept at 300°C for reduction for 40 minutes. The furnace is then cooled to room temperature to obtain a copper-based catalyst for hydrogen production by steam reforming of methanol.

[0077] Example 2 to Example 4

[0078] Embodiments 2 to 4 of the present invention respectively provide a method for preparing a copper-based catalyst for hydrogen production by steam reforming of methanol, which differs from Embodiment 1 in the masses of chromium nitrate nonahydrate and alumina powder used in step S1, as shown in Table 1 below.

[0079] Table 1 Amount of raw materials used in Examples 1 to 4

[0080]

[0081] Example 5 to Example 8

[0082] Embodiments 5 to 8 of the present invention respectively provide a method for preparing a copper-based catalyst for hydrogen production by steam reforming of methanol. The method differs from Embodiment 2 in that the masses of copper nitrate trihydrate, chromium nitrate nonahydrate and alumina powder used in step S1 are as shown in Table 2 below.

[0083] Table 2 Amounts of raw materials used in Examples 5 to 8

[0084]

[0085] Example 9 to Example 11

[0086] Embodiments 9 to 11 of the present invention respectively provide a method for preparing a copper-based catalyst for hydrogen production by steam reforming of methanol. The method differs from Embodiment 6 in that the masses of copper nitrate trihydrate, chromium nitrate nonahydrate and alumina powder used in step S1 are as shown in Table 3 below.

[0087] Table 3 Amounts of raw materials used in Examples 9 to 11

[0088]

[0089]

[0090] Example 12 to Example 17

[0091] Embodiments 12 to 17 of the present invention respectively provide a method for preparing a copper-based catalyst for hydrogen production by steam reforming of methanol, which differs from Embodiment 6 in the type and mass of the transition metal used in step S1, as shown in Table 4 below.

[0092] Table 4 Amounts of raw materials used in Examples 12 to 17

[0093] Transition metal salt types Transition metal salt dosage Load Example 12 Ammonium Metatungstate 0.105g(0.085mmol) <![CDATA[5%Cu-5%WO3]]> Example 13 Ammonium tetramolybdate 0.120 g (0.181 mmol) <![CDATA[5%Cu-5%MoO3]]> Embodiment 14 Tantalum Ethoxide 0.386 g (0.846 mmol) <![CDATA[5%Cu-5%Ta2O5]]> Embodiment 15 Niobium ethoxide 0.517 g (1.625 mmol) <![CDATA[5%Cu-5%Nb2O5]]> Example 16 Ammonium metavanadate 0.145 g (1.240 mmol) <![CDATA[5%Cu-5%V2O5]]> Embodiment 17 Chromium nitrate nonahydrate 0.527 g (1.317 mmol) <![CDATA[5%Cu-5%CrO x ]]>

[0094] Comparative Example 1

[0095] This comparative example 1 provides a method for preparing a copper-based catalyst for hydrogen production by methanol steam reforming, comprising the following steps:

[0096] S1. Weigh 0.543 g (2.25 mmol) of copper nitrate trihydrate and dissolve it in 10 mL of deionized water to prepare a copper nitrate solution, then add 1.860 g of alumina powder (needle-shaped γ-alumina purchased from Sinopharm Chemical Reagent Co., Ltd.) and mix under magnetic stirring at room temperature of 25° C. for 3 h to prepare a mixed suspension;

[0097] S2, after the mixed suspension is stirred and evaporated to dryness in a water bath at 80°C, the obtained solid is dried in a hot air drying oven at 80°C for 12 hours and after constant weight is reached, the dried solid is ground and passed through a 50-mesh sieve to obtain a catalyst precursor;

[0098] S3, transferring the catalyst precursor into a muffle furnace, heating it from room temperature to 400°C at a rate of 2°C / min in an air atmosphere, calcining it at 400°C for 4 hours, and then cooling it to room temperature with the furnace to obtain a catalytic intermediate;

[0099] S4. The catalytic intermediate is transferred to an atmosphere furnace. After the temperature is raised to 300°C at a rate of 2°C / min under an argon atmosphere and preheated for 1 hour, a 10 vol.% mixture of hydrogen and argon is introduced into the atmosphere furnace and the furnace is kept at 300°C for reduction for 40 minutes. The furnace is then cooled to room temperature to obtain a copper-based catalyst (Cu / Al2O3) for hydrogen production by methanol steam reforming.

[0100] Comparative Example 2

[0101] This comparative example 2 provides a method for preparing a copper-based catalyst for hydrogen production by methanol steam reforming, comprising the following steps:

[0102] S1. Weigh 0.543 g (2.25 mmol) of copper nitrate trihydrate and dissolve it in 10 mL of deionized water to prepare a copper nitrate solution, then add 1.860 g of chromium oxide powder and mix with magnetic stirring at room temperature of 25° C. for 3 h to prepare a mixed suspension;

[0103] S2, after the mixed suspension is stirred and evaporated to dryness in a water bath at 80°C, the obtained solid is dried in a hot air drying oven at 80°C for 12 hours and after constant weight is reached, the dried solid is ground and passed through a 50-mesh sieve to obtain a catalyst precursor;

[0104] S3, transferring the catalyst precursor into a muffle furnace, heating it from room temperature to 400°C at a rate of 2°C / min in an air atmosphere, calcining it at 400°C for 4 hours, and then cooling it to room temperature with the furnace to obtain a catalytic intermediate;

[0105] S4. The catalytic intermediate is transferred to an atmosphere furnace. After the temperature is raised to 300°C at a rate of 2°C / min under an argon atmosphere and preheated for 1 hour, a 10 vol.% mixture of hydrogen and argon is introduced into the atmosphere furnace and the furnace is kept at 300°C for reduction for 40 minutes. The furnace is then cooled to room temperature to obtain a copper-based catalyst (Cu / Cr2O3) for hydrogen production by methanol steam reforming.

[0106] Comparative Example 3

[0107] This comparative example 3 provides a method for preparing a Cu catalyst for hydrogen production by methanol steam reforming based on the Chinese patent publication number CN113145127A, comprising the following steps:

[0108] D1. Weigh 8.36 g of copper nitrate trihydrate, 24.21 g of aluminum nitrate nonahydrate, 2.48 g of 50% manganese nitrate solution and 0.48 g of zirconium nitrate pentahydrate, add 50% ethanol aqueous solution to prepare 200 mL of mixed solution; weigh 13.42 g of ammonium carbonate and add 50% ethanol aqueous solution to prepare 200 mL of ammonium carbonate solution;

[0109] D2, weighing 6.63g of alumina powder (γ-alumina) into the reactor, and uniformly adding the mixed solution and ammonium carbonate solution into the reactor through a sampling pump, stirring vigorously, aging at 60°C for 6h, and then filtering, drying the filter cake at 120°C, tableting, grinding and passing through a 40-mesh sieve to obtain a catalyst precursor;

[0110] D3. The catalyst precursor was calcined in a muffle furnace at 900°C for 3 hours and then cooled to room temperature to obtain a Cu catalyst for hydrogen production by methanol steam reforming, wherein the mass fraction of copper oxide was about 27%, the mass fraction of aluminum oxide was about 69%, and the remainder was manganese oxide and zirconium oxide.

[0111] Comparative Example 4

[0112] This comparative example 4 provides a method for preparing a copper-aluminum catalyst for methanol reforming to produce hydrogen based on the Chinese patent with publication number CN102698752A, comprising the following steps: weighing 34.2 g of copper nitrate trihydrate, 82.8 g of aluminum nitrate nonahydrate, and 106.5 g of citric acid, adding them into a three-necked flask containing 250 mL of distilled water, stirring and reacting in a 50°C water bath for 9 hours, and then evaporating the solvent, calcining the obtained solid in an air atmosphere at 800°C for 5 hours, adding 2.5 g of graphite to form sheets, and reducing the formed product at a H2 flow rate of 30 mL / min and 220°C for 6 hours to obtain a copper-aluminum catalyst for methanol reforming to produce hydrogen; wherein the copper oxide mass fraction in the copper-aluminum catalyst is approximately 45%, the aluminum oxide mass fraction is approximately 45%, and the remainder is graphite carbon.

[0113] Comparative Example 5

[0114] This comparative example 5 provides a method for preparing a catalyst for hydrogen production by steam reforming of methanol based on Chinese patent publication number CN102872867A, comprising the following steps:

[0115] D1. Weigh 0.890 g of palladium chloride, 9.970 g of zinc nitrate hexahydrate and 0.746 g of scandium nitrate hexahydrate, mix and dissolve them in 50 mL of deionized water to prepare solution A; dissolve 13.250 g of anhydrous sodium carbonate in 125 mL of deionized water to prepare solution B;

[0116] D2. Pre-load 10 mL of solution B in a beaker, inject solution A into the beaker at a rate of 18 mL / min, continue stirring in a 60°C water bath for coprecipitation reaction, and adjust the pH of the reaction solution in the beaker to 9-10 by adding solution B; after adding solution A and solution B, continue stirring for 30 minutes and filter, wash with deionized water until the sodium ion concentration in the washing solution is less than 0.1 ppm, and then separate by suction;

[0117] D3. The separated solid was mixed with 0.298 g CNT and slurried at room temperature for 4 hours, followed by centrifugal filtration. The solid was dried at 110°C for 10 hours, transferred to 360°C for calcination for 2 hours, and then cooled to room temperature to obtain a catalytic intermediate. The catalytic intermediate was reduced at normal pressure, a hydrogen flow rate of 30 mL / min, and 250°C for 5 hours to obtain a catalyst for hydrogen production by methanol steam reforming.

[0118] Structural characterization

[0119] The catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were characterized by XRD. Figure 1 As shown; the catalytic intermediates prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were characterized by Raman spectroscopy. Figure 2 The catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to nitrogen adsorption and desorption tests, and the specific surface areas were measured as shown in Table 5 below; the catalytic intermediates prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to hydrogen temperature programmed reduction (H2-TPR) tests, and the test results were as shown in Table 5 below. Figure 3 shown.

[0120] Table 5 Specific surface area of ​​catalysts in Examples 1 to 4 and Comparative Examples 1 to 2

[0121]

[0122]

[0123] from Figure 1 It can be seen that the diffraction peaks of Al2O3 and Cu can be observed on the catalysts of Example 1 and Example 2, but no diffraction peaks of CrO X The diffraction peak of Cu is weak, which indicates that by adding CrO X It can promote the dispersion of Cu on the surface of Al2O3, which is beneficial to improve the uniformity of Cu on the carrier; while in Examples 3 and 4, the diffraction peak of Al2O3 can be observed, but the diffraction peak of CrO X and Cu diffraction peaks, which indicates that the adjustment of CrO XThe amount of can adjust its effect of promoting the dispersion of Cu. In Comparative Example 1, obvious diffraction peaks of Al2O3 and Cu can be observed, which indicates that the Cu component is highly aggregated and has a high crystallinity.

[0124] Combination Figure 1 and Figure 2 It can be seen that compared with Comparative Example 1, the characteristic peaks of the Cu(111) crystal plane in the catalysts prepared in Examples 1 to 4 increase with the increase of CrO X The peak of Cu(111) crystal surface gradually decreases with the increase of CrO X It can promote the uniform dispersion of Cu on the surface of Al2O3 and reduce the grain size of Cu, thereby effectively increasing the number of catalytic active sites of Cu in the catalyst. Figure 2 It can be seen from the Raman spectrum in the catalysts of Examples 1 to 4 that CrO X Displayed as Cr 6+ , and no vibration band of CuO was observed, which indicates that CrO X It mainly exists in the form of a high-valent state, while in Comparative Example 2, Cr in the catalyst mainly exists in the form of a low-valent state.

[0125] Performance Testing

[0126] The catalysts prepared in Examples 1 to 17 and Comparative Examples 1 to 2 were subjected to methanol steam reforming to produce hydrogen, comprising the following steps: 100 mg of the in-situ reduced catalyst was placed in a fixed bed straight quartz tube reactor, the temperature was raised to 200° C. under a nitrogen atmosphere, a methanol-water mixture (methanol to water molar ratio of 1:1.5) was introduced into a vaporization chamber at a flow rate of 0.05 mL / min using a high-pressure constant flow pump, and 30 mL / min of argon was used as a carrier gas to introduce the methanol-water vapor mixture at a flow rate of 27 h. -1 The gas was passed into a quartz tube reactor at a mass time-space velocity of 1.5 wt % and reacted stably at 200, 220, 240 and 260 °C for 30 min respectively under normal pressure. The steady-state products at each temperature were collected and separated using a GC9310 gas chromatograph equipped with a TDX-01 chromatographic column and a TCD detector to detect changes in the concentrations of H2, CO2 and CO. The evaluation results are shown in the figure. Figures 4 to 7 shown.

[0127] The catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were heated at normal pressure, a reaction temperature of 260° C., and a methanol-water vapor mixed gas mass space time velocity of 27 h -1The catalytic reaction was carried out under the condition that the molar ratio of methanol to water in methanol-water vapor was 1:1.5, and the concentration changes of H2, CO2 and CO in the reaction products were detected. The methanol conversion rate, carbon dioxide selectivity, carbon monoxide selectivity and hydrogen production rate (mmol H2 g cat -1 h -1 ), as shown in Tables 6 and 7 below.

[0128] The catalyst prepared in Example 2 was heated at normal pressure, reaction temperature of 260°C, and a mass space time velocity of methanol-water vapor mixture of 27 h -1 , methanol and water in methanol vapor with a molar ratio of 1:1.5, the catalytic reaction was continued for 90 h and the hydrogen production rate (mmol H2 g cat -1 h -1 ) curve and methanol conversion rate as shown in Figure 8 shown.

[0129] Table 6 Comparison of catalyst performance of Examples 1 to 4 and Comparative Examples 1 to 2

[0130] Methanol conversion rate / % <![CDATA[CO2 Selectivity / %]]> CO volume concentration / ppm Hydrogen production rate Example 1 80.6 99.2 2.0 1105.8 Example 2 94.3 99.7 1.1 1293.8 Example 3 92.9 99.3 1.7 1274.6 Example 4 84.3 98.8 3.0 1156.6 Comparative Example 1 76.8 95.6 13.2 1053.7 Comparative Example 2 51.8 93.2 18.7 710.7

[0131] Table 7 Comparison of catalyst performance of Example 2, Comparative Examples 3 to 5

[0132] Methanol conversion rate / % CO selectivity / % Calcination temperature / ℃ Example 2 94.3 0.30 400 Comparative Example 3 88.2 0.85 900 Comparative Example 4 85.2 0.33 800 Comparative Example 5 66.8 1.00 360

[0133] It can be seen from Table 6 that the catalysts provided by Examples 1 to 4 of the present invention have excellent catalytic activity, low CO content, and high hydrogen production rate. Figure 3 It can be seen that Example 2 has a lower reduction temperature than Comparative Example 1, and CuO and CrO x The reduction temperature of Figure 8 It can be seen that after the reaction lasted for 90 hours, the activity and hydrogen production rate were still maintained at a high level.

[0134] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A copper-based catalyst for hydrogen production by methanol steam reforming, characterized in that: include: A porous carrier and a copper complex and a transition metal oxide loaded on the surface of the porous carrier; The loading amount of the copper element in the copper complex on the copper-based catalyst is 5-30%; The molar ratio of the copper element in the copper composite to the transition metal element in the transition metal oxide is (0.1-1.8):

1.

2. The copper-based catalyst according to claim 1, characterized in that: The copper composite includes elemental copper nanoparticles; And / or, the copper composite is generated by reducing copper oxide under a reducing atmosphere; And / or, the transition metal element in the transition metal oxide is at least one of chromium, niobium, tantalum and vanadium; And / or, the transition metal oxide includes transition metal ions in at least two valence states.

3. The copper-based catalyst according to claim 1, characterized in that: The porous carrier includes at least one of an alumina carrier, a cerium oxide carrier, a zirconium oxide carrier, a molybdenum carbide carrier, a silicon dioxide carrier, and a molecular sieve; And / or, the specific surface area of ​​the porous carrier is 180-200m 2 / g; And / or, the source of the copper complex includes at least one of copper nitrate, copper sulfate, and copper chloride; And / or, the source of the transition metal oxide includes at least one of a transition metal nitrate and a transition metal organic salt.

4. A method for preparing a copper-based catalyst as claimed in any one of claims 1 to 3, characterized in that: include: The porous carrier is mixed in a mixed solution of copper ions and transition metal ions, and the solvent is evaporated to obtain a catalyst precursor, and the catalyst precursor is oxidized at high temperature and then reduced to obtain a copper-based catalyst.

5. The preparation method according to claim 4, characterized in that: The molar ratio of copper ions to transition metal ions in the mixed solution is (0.1-1.8):1; and / or, mixing the porous carrier in a mixed solution at 20-30° C.; and / or, mechanically mixing the porous carrier in the mixed solution for 2-3 hours and then evaporating the solvent, wherein the mechanical mixing includes one of ultrasonic mixing, stirring mixing and oscillating mixing; and / or, after mixing the porous carrier in the mixed solution, evaporating the solvent at 75-90° C.; and / or, evaporating the solvent and then drying to obtain a catalyst precursor; and / or, evaporating the solvent and grinding through a 40-60 mesh screen to obtain a catalyst precursor; And / or, the average particle size of the catalyst precursor is 250-380 μm.

6. The preparation method according to claim 4, characterized in that: Oxidizing the catalyst precursor in an oxygen-containing atmosphere at 350-450° C.; and / or, oxidizing the catalyst precursor at high temperature for 3-5h; and / or, the catalyst precursor is subjected to high temperature oxidation and then reduced in a reducing atmosphere having a hydrogen content of 5-15 vol.%; and / or, the catalyst precursor is subjected to high temperature oxidation and then reduced in a reducing atmosphere for 30-50 minutes; And / or, the catalyst precursor is subjected to high temperature oxidation and then reduced in a reducing atmosphere at 250-350°C.

7. Use of the copper-based catalyst according to any one of claims 1 to 3 or the copper-based catalyst prepared by the preparation method according to any one of claims 4 to 6 in hydrogen production by steam reforming of methanol.

8. The use according to claim 7, characterized in that: include: At 200-260℃, under the catalysis of copper-based catalyst, methanol and water vapor mixed gas is introduced to react and generate hydrogen.

9. The use according to claim 8, characterized in that: The methanol-water vapor mixed gas includes an inert carrier gas; and / or, the molar ratio of methanol to water in the methanol-water vapor mixture is 1:(1-2); and / or, reacting under the catalysis of a copper-based catalyst to generate hydrogen, carbon dioxide and carbon monoxide, wherein the volume fraction of the carbon monoxide is less than or equal to 3 ppm; And / or, methanol-water vapor mixture is heated for 20-30 hours -1 The weight airspeed is entered.

Citation Information

Patent Citations

  • Copper-aluminum catalyst for hydrogen production by methanol reforming, and preparation method and application thereof

    CN102698752A

  • Catalyst used for hydrogen production by methanol steam reforming and preparation method of catalyst

    CN102872867A

  • Cu catalyst for hydrogen production by methanol steam reforming and preparation method and application thereof

    CN113145127A